Plantas medicinais na prática do trabalho cotidiano dos agentes comunitários de saúde de limoeiro do norte – CE: conhecer para transformar - Mendes, Maria Zilná Arrais Daniel (2020)
The World Health Organization (WHO) defines Medicinal Plants as any and all vegetables that contain, in one or more organs, substances that can be used for therapeutic purposes or that are precursors of semi-synthetic drugs. The present study, with the quantitative approach, of a descriptive type, with action-research procedures, aimed to evaluate the knowledge about Medicinal Plants in the daily work practice of community health agents (CHA) in Limoeiro do Norte - CE, in search of know to transform. One hundred and three (103) CHA participated in the study. The level of knowledge of the CHA on Medicinal Plants was previously evaluated, revealing that 59.2% had not participated in courses on Medicinal Plants, 89.3% use Medicinal Plants and 71.8% instruct the population to use, it is worth to highlight that the influence of use is due to the family and people in the community; 96.1% believe in efficacy, 90.3% that the low cost does not interfere with effectiveness, 83.5% do not know people whose use of plants has caused harm to health, 57.3% know people cured through use, being the most used plants in the communities where they operate: pomegranate, boldo, mastruz, mint and althaea. In addition, a training was performed that provided the construction of theoretical knowledge about Medicinal Plants in natura and practical experiences on the preparation of home remedies. In this context, it was evaluated and evidenced that there was an increase from 12% to 54% in terms of safety in guiding people on the use of Medicinal Plants; from 29% to almost 59% of plants cited by REPLAME - CE. The high level of correct answers regarding the hygiene techniques, method of use, preparations, indication and contraindication demonstrate the achievement of the proposed objectives. It was concluded that the training workshop was effective in empowering CHAs in theoretical and practical knowledge to guide individuals and families regarding the effective and safe use of Medicinal Plants in health care. It is necessary to understand that the workshop will not supply the acquisition of knowledge by the CHA, so it is important to implement Permanent Education in Medicinal Plants and herbal medicines with local programming that responds to the needs of primary care. Furthermore, the actions of the Living Pharmacy Program and the activities of professional practice by Community Health Agents are inserted in prevention and health promotion activities, justifying the practice of guiding the use of Medicinal Plants, as long as it has the knowledge to guarantee quality of care and the transformation of professional practice.